URGENSI KONSEP AL-‘ARIYAH, AL-QARDH, DAN AL-HIBAH DI INDONESIA - Johan Alamsyah (Yurisprudentia: Jurnal Hukum Ekonomi, 2018)
Humans are creatures of Allah SWT who are weak, so that a human being will not be able to live alone without others, especially in Islamic teachings other than the command to establish hablumminallah (relationship to Allah SWT) also ordered to establish hablumminannas (relations to humans), then in the scientifically, a human being is often referred to as a social being because human beings between one another need each other, help each other and exchange each other to make ends meet both by buying and selling, renting, borrowing and borrowing individual or group, it cannot even be denied that in daily life as a human being, the need for something will always be there because it is a human being and always lives in a society.So the existence of the terminology of al-‘ariyah, al-qardh, and al-grant cannot be absorbed in the life of human beings and has even become a part of human life in the world